Behavioral Analysis of Genetically Modified Mice Indicates Essential Roles of Neurosteroidal Estrogen - Harada, Nobuhiro; Wakatsuki, Toru; Honda, Shin-ichiro (Frontiers in Endocrinology, 2011)
Brain aromatase is expressed only in the nerve cells of specific brain regions with a transient peak at the neonatal period when sexual behaviors become organized. Aromatase knockout (ArKO) mouse, generated to give light on the physiological functions of estrogen in the brain, exhibited various abnormal behaviors, concomitant with undetectable estrogen and increased androgen in the blood. To further elucidate effects of neurosteroidal estrogens on the behavioral phenotypes, we first prepared an aromatase transgenic (bsArTG) mouse by introduction of a human aromatase transgene controlled under a 6.5 kb upstream region of the brain-specific promoter of mouse aromatase gene into fertilized mouse eggs, because the -6.5 kb promoter region was previously showed to contain the minimal essesntial element responsible for the brain-specific spatiotemporal expression. Then, an ArKO mouse expressing the human aromatase only in the brain was generated by crossing of bsArTG mouse with ArKO mouse. The resulting mice (ArKO/bsArTG mice) nearly recovered from abnormal sexual, aggressive, and locomotive (exploratory) behaviors, in spite of almost the same serum levels of estrogen and androgen in the adulthood as ArKO mouse. These results suggest that estrogens locally synthesized in the specific neurons of the perinatal mouse brain are a major factor to directly act on the neurons and play crucial roles in the organization of neuronal networks participating in the control of sexual, aggressive, and locomotive (exploratory) behaviors.